Process writing as reading comprehension tool for expository text in social studies - Alcazar, Marie Yvette Concepcion (2006)
The study determined the relationship of process writing with reading comprehension. The subjects, 34 second grade students of a State school in Quezon Cuty, who are about 8 1/2 years old, underwent a 6-week experimental study to compare the reading comprehension of students who used process writing as a post reading approach and those who don't. A set of teacher-made comprehension tests were given after the post reading activities. Results showed that both writing methods are useful in improving the reading comprehension of Social Studies text. The qualitative analysis of the writing samples also showed that the quality of the product of process writing was better because it showed more details from the text, there was incorporation of new knowledge with prior knowledge, and it demonstrated multi-level comprehension.